2013
DOI: 10.1214/13-aos1159
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating nonconvex penalized regression in ultra-high dimension

Abstract: We investigate high-dimensional non-convex penalized regression, where the number of covariates may grow at an exponential rate. Although recent asymptotic theory established that there exists a local minimum possessing the oracle property under general conditions, it is still largely an open problem how to identify the oracle estimator among potentially multiple local minima. There are two main obstacles: (1) due to the presence of multiple minima, the solution path is nonunique and is not guaranteed to conta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
149
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(150 citation statements)
references
References 37 publications
0
149
0
Order By: Relevance
“…More recently, Wang et al (2013) proposed a two-step approach named calibrated CCCP which achieve strong oracle properties when using the Lasso estimator as initialization. Our work differs from theirs in two aspects.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…More recently, Wang et al (2013) proposed a two-step approach named calibrated CCCP which achieve strong oracle properties when using the Lasso estimator as initialization. Our work differs from theirs in two aspects.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Recently, Fan et al [9] have shown that the folded concave penalization methods enjoy the strong oracle property for high-dimensional sparse estimation. Important insight has also been gained through the recent work on theoretical analysis of the global solution [19][20][21].…”
Section: Journal Of Probability and Statisticsmentioning
confidence: 99%
“…Recently, Dicker et al [6] proposed a BIC-like tuning parameter selector. Wang et al [21] extended the work of [24,25] for BIC on highdimensional least squares regression; they proposed a highdimensional BIC for a nonconvex penalized solution path.…”
Section: Journal Of Probability and Statisticsmentioning
confidence: 99%
“…The class of nonconvex penalties includes MCP (Zhang, 2010a), SCAD (Fan and Li, 2001), and capped-L 1 penalty (Zhang, 2010b), among others. The estimation consistency and oracle properties of the nonconvex estimators are investigated by Fan et al (2012); Fan and Lv (2011); Loh and Wainwright (2013); Wang et al (2013a); Zhang et al (2013); Wang et al (2013b). Though significant progress has been made towards understanding the estimation theory for high dimensional models, how to quantify the uncertainty of the obtained penalized estimators remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%